Development of Pb-free solder for electronic assembly - Li, Guoyuan. (2008)
This project aimed (1) to look for new lead-free solder alloy systems with improved properties for electronic packaging and assembly, (2) to study the effects of microstructural evolution on the reliability of the solder joints, and (3) to investigate the growth kinetics of the IMC formation in solder joints based on establishing new theoretical model.